UNDERSTANDING THE INTERACTION BETWEEN GLUTATHIONE AND ACETAMINOPHEN: A DOCKING STUDY APPROACH - Mohammad Rizki Fadhil Pratama; Eko Suhartono (Dentino : Jurnal Kedokteran Gigi, 2018)
Background:Acetaminophen (PCT) is known for its pro-oxidant properties, which neutralized by the presence of internal antioxidants such as glutathione (GSH). GSH has two forms: monomers and dimers, mainly distinguished by the presence of thiol group. Purpose:This study aims to see the difference in interaction between PCT with both forms of GSH. Method:Molecular docking was performed using Autodock Vina 1.1.2 on whole GSH surfaces. The main parameter used was the free energy of binding as affinity marker, as well as the position of PCT toward GSH. Result:The docking results show that PCT has a slightly higher affinity to the dimeric form of GSH than its monomeric form with the free energy of binding -2.7 kcal/mol and -2.2 kcal/mol, respectively. The interesting thing is the acetyl group of PCT is in a position far from the thiol group in the monomeric form of GSH, in contrast to its dimeric form. Conclusion:These results show that difference in affinity of PCT to both GSH forms is influenced by the position of the acetyl group against the thiol group of cysteine in GSH. The proximity of the pro-oxidant group to the thiol group leads to an increase in the affinity of the pro-oxidant to GSH.